2020
DOI: 10.3390/nu12051360
|View full text |Cite
|
Sign up to set email alerts
|

Momentary Physical Activity Co-Occurs with Healthy and Unhealthy Dietary Intake in African American College Freshmen

Abstract: Background: Research investigating interrelations between physical activity and dietary intake has primarily used retrospective, summary-based measures of behavior subject to increased recall bias. This study used ecological momentary assessment (EMA) methods with accelerometry to determine within-day, momentary associations between physical activity and dietary intake behaviors in African American college freshmen. Methods: Participants (N = 50) completed a dietary EMA protocol that assessed food/fluids consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(52 citation statements)
references
References 45 publications
0
46
0
Order By: Relevance
“…Previous studies indicated that habitual Mediterranean dietary pattern is associated with more time spent on leisure-time physical activity among older adults (19). Momentary physical activity was concomitant with momentary consumption of both healthy and unhealthy dietary intake in college students (20). Thus, it is hypothesized that dietary status may play a contributory role in the association of physical activity with gut microbiota.…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies indicated that habitual Mediterranean dietary pattern is associated with more time spent on leisure-time physical activity among older adults (19). Momentary physical activity was concomitant with momentary consumption of both healthy and unhealthy dietary intake in college students (20). Thus, it is hypothesized that dietary status may play a contributory role in the association of physical activity with gut microbiota.…”
Section: Introductionmentioning
confidence: 98%
“…This study was part of a larger study that utilized ecological momentary analysis to assess the relationships between physical activity and dietary intake in African–American college freshman over the course of 7 consecutive days [ 39 ]. For the purposes of this study, we are including data collected at an introductory session on day 1 and dietary recalls and urine collected on days 4, 5, and 6.…”
Section: Methodsmentioning
confidence: 99%
“…Second, the associated impact of prolonged exercise and environmental heat stress on urinary hydration markers impedes the ability to fully understand the relationships between nutrient intake and urinary hydration biomarkers. Here, we adapt the approach taken by Muñoz et al, in application to data collected in the Freshman Reports of Eating, Exercise, Sitting and Health (FRESH) study [ 39 ]. Our specific objective was to identify hydration-related nutrients that were consumed concomitantly in a population of free-living African American emerging adults enrolled in their first semester (Fall semester) of college in the Southeastern United States.…”
Section: Introductionmentioning
confidence: 99%
“…However, dietary intake typically does not occur within each predefined time-interval (e.g. no intake in 46% of 2-h-time-intervals [ 7 ]) or only a small amount is consumed (e.g. a snack).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a common approach is to study whether but not how much dietary intake occurred through multilevel logistic regressions (e.g. [ 7 , 12 14 ]). However, if the amounts of the consumed foods/drinks are also captured, available data with important implications are disregarded.…”
Section: Introductionmentioning
confidence: 99%